Rab27a targeting to melanosomes requires nucleotide exchange but not effector binding - Tarafder, Abul K. (2022)
Rab GTPases are important determinants of organelle identity and regulators of vesicular transport pathways. Consequently, each Rab occupies a highly specific subcellular localization. However, the precise mechanisms governing Rab targeting remain unclear. Guanine nucleotide exchange factors (GEFs), putative membrane-resident targeting factors and effector binding have all been implicated as critical regulators of Rab targeting. Here, we address these issues using Rab27a targeting to melanosomes as a model system. Rab27a regulates motility of lysosome-related organelles and secretory granules. Its effectors have been characterized extensively, and we have identified Rab3GEP as the non-redundant Rab27a GEF in melanocytes (Figueiredo AC et al. Rab3GEP is the non-redundant guanine nucleotide exchange factor for Rab27a in melanocytes. J Biol Chem 2008;283:23209-23216). Using Rab27a mutants that show impaired binding to representatives of all four Rab27a effector subgroups, we present evidence that effector binding is not essential for targeting of Rab27a to melanosomes. In contrast, we observed that knockdown of Rab3GEP resulted in mis-targeting of Rab27a, suggesting that Rab3GEP activity is required for correct targeting of Rab27a. However, the identification of Rab27a mutants that undergo efficient GDP/GTP exchange in the presence of Rab3GEP in vitro but are mis-targeted in a cellular context indicates that nucleotide loading is not the sole determinant of subcellular targeting of Rab27a. Our data support a model in which exchange activity, but not effector binding, represents one essential factor that contributes to membrane targeting of Rab proteins.